Prevalence of the serpin peptidase inhibitor (alpha-1-antitrypsin) PI*S and PI*Z alleles in Brazilian children with liver disease - Baldo,Guilherme (2008)
Serpin peptidase inhibitor, clade A (alpha-1 antiproteinase, antitrypsin), member 1 (SERPINA1) deficiency is one of the main genetic causes related to liver disease in children. In SERPINA1 deficiency the most frequent SERPINA1 alleles found are the PI*S and PI*Z alleles. We used the polymerase chain reaction and the amplification created restriction site (ACRS) technique to investigate the prevalence of the PI*S and PI*Z alleles in a group of Brazilian children (n = 200) with liver disease and established the general frequency of the PI*S allele in our population. We found a significant association of the PI*Z allele and liver disease, but no such relationship was found for the PI*S allele. Our results show that SERPINA1 deficiency due to the PI*Z allele, even when heterozygous, is a frequent cause of liver disease in our group of Brazilian children but that the PI*S allele does not confer an increased risk of hepatic disorders in our group of Brazilian children.